Tourism and ecological protection status of the Aksu-Zhabagly world heritage site of Kazakhstan (Journal of Geography and Environmental Management, 2020)
Nowadays, the Protected Areas have become major destinations for rapidly growing tourism and recreational activities for its natural beauty, rare species of wildlife, and historical and cultural heritage sites.The article considers environmental issues of the Aksu-Zhabagly World Natural Heritage Site with high tourist and recreational potential. Objects of world heritage are widely known all over the world. It often attracts the attention of the tourism industry, especially travel agencies, tourism organizers and tourists. There is no doubt that following the relevant law on Specially Protected Areas, the development of some types of tourism in the buffer zones of the reserve is beneficial for the effective protection of the territory. The results of the analysis of materials related to the protection of the Aksu-Zhabagly State Nature Reserve show that the protected area has been efficiently protected under various laws of Spe-cially Protected Areas. Besides, every year many events are held to preserve the original ecology of the reserve. One of them is the organization of various types of tourism, which, on the one hand, increases the importance of protecting the reserve, on the other hand, helps to raise funds for the protection of the reserve. We also noticed that sometimes international events are organized to protect the reserve, and sometimes financial support is provided by international organizations. We also found that sometimes international events are organized to protect the reserve, and sometimes financial support is provided by international organizations as well. One of the key issues identified in the article is the environmental safety of the reserve - the incomplete implementation of some projects for the protection of the reserve. This issue needs further study.